2008
DOI: 10.1172/jci34672
|View full text |Cite
|
Sign up to set email alerts
|

VAMP8 is the v-SNARE that mediates basolateral exocytosis in a mouse model of alcoholic pancreatitis

Abstract: In rodents and humans, alcohol exposure has been shown to predispose the pancreas to cholinergic or viral induction of pancreatitis. We previously developed a rodent model in which exposure to an ethanol (EtOH) diet, followed by carbachol (Cch) stimulation, redirects exocytosis from the apical to the basolateral plasma membrane of acinar cells, resulting in ectopic zymogen enzyme activation and pancreatitis. This redirection of exocytosis involves a soluble NSF attachment receptor (SNARE) complex consisting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
117
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(131 citation statements)
references
References 55 publications
11
117
1
1
Order By: Relevance
“…We previously reported that pancreatic acini employed Munc18c-Syn-4-VAMP8-SNAP23 as the putative SM-SNARE complex mediating basolateral exocytosis that causes pancreatitis [25][26][27]. We showed that all beta cell Syns displayed promiscuous binding to VAMP2 and VAMP8 and to SNAP25 and SNAP23, although each Syn has a preference for a particular VAMP [16,17].…”
Section: Syn-4 Depletion Diminishes Biphasic Gsis By Reducing Exocytomentioning
confidence: 87%
“…We previously reported that pancreatic acini employed Munc18c-Syn-4-VAMP8-SNAP23 as the putative SM-SNARE complex mediating basolateral exocytosis that causes pancreatitis [25][26][27]. We showed that all beta cell Syns displayed promiscuous binding to VAMP2 and VAMP8 and to SNAP25 and SNAP23, although each Syn has a preference for a particular VAMP [16,17].…”
Section: Syn-4 Depletion Diminishes Biphasic Gsis By Reducing Exocytomentioning
confidence: 87%
“…insulin secretion in diabetes, mast cell secretion in allergic reactions) [28]. One mode is fusion of secretory granules, either by orderly sequential fusion as in pancreatic acinar cells [13,20] or by prior homotypic fusion leading to compound exocytosis, as in mast cells [35]. Islet beta cells employ fusion of secretory granules [31,36], but to a much lesser extent than other secretory cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is of importance, as first-phase GSIS is much reduced in patients with type 2 diabetes, and this has been attributed in part to greatly reduced islet SYN-1A levels [23], along with reduction of cognate SNAREs (SNAP25 and VAMP2) and the Sec1/Munc18-like protein (SM) Munc18a. SYN-3 was shown in pancreatic acinar cells to preferentially form complexes with VAMP8 [20] and Munc18b [38,39], which are also present in beta cells [40][41][42]. We recently reported, employing the Vamp8-knockout mice [43], that VAMP8 also mediated the recruitment and fusion of newcomer SGs, and was the putative cognate v-SNARE that binds SYN-3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence implicating FAEEs as important mediators of the crucial intracellular trypsinogen activation initiating alcoholrelated pancreatitis does not exclude other effects of alcohol (16,17). In view of the variable acute effects of ethanol itself on isolated pancreatic acinar cells (8) we have carried out a detailed study of the action of alcohol, using two-photon permeabilized cells, which have turned out to be useful preparations for studies of Ca 2+ homeostasis (12,18,19).…”
mentioning
confidence: 99%